2012
DOI: 10.1100/2012/359413
|View full text |Cite
|
Sign up to set email alerts
|

Plant Regeneration and Cellular Behaviour Studies inCelosia cristataGrownIn VivoandIn Vitro

Abstract: Tissue culture studies of Celosia cristata were established from various explants and the effects of various hormones on morphogenesis of this species were examined. It was found that complete plant regeneration occurred at highest percentage on MS medium supplemented with 2.0 mg/L NAA and 1.5 mg/L BAP, with the best response showed by shoot explants. In vitro flowering was observed on MS basal medium after six weeks. The occurrence of somaclonal variation and changes in cellular behavior from in vivo and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 9 publications
(10 reference statements)
3
16
0
Order By: Relevance
“…Surface Sterilization C. argentea sterilization protocol was optimized with minor modification from Taha and Wafa (2012). Five different sets were used by adjusting the time and concentrations of sodium hypochlorite and mercury chloride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface Sterilization C. argentea sterilization protocol was optimized with minor modification from Taha and Wafa (2012). Five different sets were used by adjusting the time and concentrations of sodium hypochlorite and mercury chloride.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the friable callus were obtained from leaf explants. Previous study (Taha and Wafa 2012) had shown to have white, yellow, orange, green and black callus in C. cristata. All the explants were able to produce reddish purple callus on MS medium containing 0.5-2.0 mg/L BAP and 0.5 mg/L NAA.…”
Section: Callus Inductionmentioning
confidence: 99%
“…The seeds were then soaked in 70%, 50%, 30% and 20% (v/v) sodium hypochlorite for 5 minutes one by one. Then, the seeds were rinsed with distilled water for three times [2]. In laminar flow chamber, the seeds were dipped in 70% (v/v) ethanol for 1 minute and rinsed with sterile distilled water for three times.…”
Section: Methodsmentioning
confidence: 99%
“…Celosia spp. are amenable in tissue culture and all C. crispate explant sources could regenerate or were able to produce shoots in-vitro [2] whereas, in V. Faber, it is comparatively more difficult to induce callus and regeneration in-vitro [8].…”
Section: Taf Publishingmentioning
confidence: 99%
“…Cytological studies, that is, measurements of the mitotic index (MI), mean cell and nuclear areas, chromosome count, and cell doubling time (Cdt), were carried out to elucidate any differences or changes that occurred in in vivo and in vitro grown D. caryophyllus plants at the cellular level, enabling the easy and early detection of somaclonal variations. Cytology facilitates chromosomal and cell division studies in plants [6] as well as enables the detection of embryogenic callus from nonembryogenic callus [7] and in vitro flowering [8, 9]. Thus, the aims of the present study are to compare at the cellular level the characteristics of tissues obtained from in vivo and in vitro environments, to detect any cellular changes when cells are transferred from the in vivo to the in vitro system, and to detect any occurrence of somaclonal variation at the cellular level.…”
Section: Introductionmentioning
confidence: 99%